2013
DOI: 10.18553/jmcp.2013.19.9.789
|View full text |Cite
|
Sign up to set email alerts
|

Cost Implications of Formulary Decisions on Oral Anticoagulants in Nonvalvular Atrial Fibrillation

Abstract: In the European Union, 4.5 million people are estimated to have AF.2 Patients with untreated AF are at a 4-to 5-fold increased risk of stroke compared with those without the disease. Vitamin K antagonists (VKAs), such as warfarin, have been successfully used for many years to provide prophylaxis against stroke in patients with AF. A large meta-analysis of randomized trials showed that adjusted-dose warfarin reduced the incidence of stroke by 64%. 4 However, in a real-world analysis of Medicare patients with AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…[19][20][21][22][23] Acquisition costs for these drugs are higher than for warfarin, but a cost-benefit review of treatment for atrial fibrillation, based on observational studies, suggested that the overall cost of therapy may be lower because, in contrast to warfarin, dose adjustment and routine monitoring of the anticoagulant effect are not required, and the risk of complications from therapy over the long term may be lower. 51 However, cost-effectiveness comparisons of non-vitamin K antagonist agents versus warfarin are warranted before the results can be directly applied to the real-world setting. …”
Section: Guidelines and Management Initiativesmentioning
confidence: 99%
“…[19][20][21][22][23] Acquisition costs for these drugs are higher than for warfarin, but a cost-benefit review of treatment for atrial fibrillation, based on observational studies, suggested that the overall cost of therapy may be lower because, in contrast to warfarin, dose adjustment and routine monitoring of the anticoagulant effect are not required, and the risk of complications from therapy over the long term may be lower. 51 However, cost-effectiveness comparisons of non-vitamin K antagonist agents versus warfarin are warranted before the results can be directly applied to the real-world setting. …”
Section: Guidelines and Management Initiativesmentioning
confidence: 99%
“…Both INR testing and the consequences of poor INR control consume considerable health care resources. [11][12][13] Dabigatran, 14 a direct thrombin inhibitor, is an OAC approved by the Food and Drug Administration in the United States in October 2010 to reduce the risk of stroke and systemic embolism in patients with nonvalvular atrial fibrillation (NVAF), which represents approximately 95% of AF cases. 15 Dabigatran offers several advantages over warfarin.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, warfarin has known interpatient variability, and numerous drug, food, and disease interactions requiring frequent laboratory monitoring, which is highly dependent on patient compliance and can increase cost. 10,[26][27][28] In reality, patient compliance may play a significant role in the frequency of laboratory follow-up, leading to an increase in health care costs. Therefore, the new agents are attractive alternatives to warfarin for some patients.…”
Section: Discussionmentioning
confidence: 99%